I.YUSUPOVTÍŃ EPIKALÍQ SHÍǴARMALARÍNDA MIFLIK MOTIVLERDIŃ QOLLANÍLÍWÍ (“Máńgi bulaq” poeması mısalında) - Qudiyarova, R. (SCIENCE and SOCIETY, 2022)
The article discusses the features of the use of mythical motifs in the epic works of the Karakalpak poet I. Yusupov. There are several studies of mythical motifs in Karakalpak literature, but the study of mythical motifs used in the epic works of I. Yusupov is one of the topical issues in literature. In this article, along with the mythical motifs used in the poet's epic works, his mastery of their use is studied.
Keywords: Myth; motif; plot; ethnogenetics; poem; fairy tale; symbolic image